TM2D3, a mammalian homologue of Drosophila neurogenic gene product Almondex, regulates surface presentation of Notch receptors - Wataru Masuda; Tomoko Yamakawa; Rieko Ajima; Katsuya Miyake; Toshifumi Umemiya; Kazuhiko Azuma; Jun-ichi Tamaru; Makoto Kiso; Puspa Das; Yumiko Saga; Kenji Matsuno; Motoo Kitagawa (Scientific Reports, 2023)
Abstract Notch signaling is an evolutionarily conserved mechanism required for numerous types of cell fate decisions in metazoans. It mediates short-range communication between cells with receptors and ligands, both of which are expressed on the cell surfaces. In response to the ligand-receptor interaction, the ligand and the extracellular domain of the Notch receptor (NECD) in the complex are internalized into ligand-expressing cells by endocytosis, a prerequisite process for the conformational change of the membrane proximal region of Notch to induce critical proteolytic cleavages for its activation. Here we report that overexpression of transmembrane 2 (TM2) domain containing 3 (TM2D3), a mammalian homologue of Drosophila melanogaster Almondex (Amx), activates Notch1. This activation requires the ligand-binding domain in Notch1 and the C-terminal region containing TM2 domain in TM2D3. TM2D3 physically associates with Notch1 at the region distinct from the ligand-binding domain and enhances expression of Notch1 on the cell surface. Furthermore, cell surface expression of Notch1 and Notch2 is reduced in Tm2d3-deficient cells. Finally, amx-deficient Drosophila early embryos exhibit impaired endocytosis of NECD and Delta ligand, for which surface presentation of Notch is required. These results indicate that TM2D3 is an element involved in Notch signaling through the surface presentation.